Estudio del espesor de la mucosa del trígono retromolar con el objetivo de facilitar la planificación de mini implantes en la región - Alves, Nilton [UNESP]; Nascimento, Carlos Manuel de Oliveira (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2012)
The retromolar triangle is a triangular area located in the mandible, posteriorly to the last molar. This region, due its thickness and bone density, is widely used for the installation of devices that provide an anchorage system for the movement of the lower molars. The aim of this research is to provide morphometric data of the mucosa thickness of the retromolar triangle. Twenty-five patients of portuguese nationality, with indication for extraction of the impacted lower third molar (right and/or left), were studied. In the region of the retromolar triangle were demarcated 3 points corresponding to the vertices of a triangle whose the base was torned for the distal face of the lower third molar and the lenght of the sides corresponded to vestibulolingual dimension of the same tooth, then was demarcated a fourth point corresponding to the geometric center of the triangle. Then, using a finger spreader with silicone stop were measured the mucosal tickness at each point. The data obtained were tabulated and analyzed. The lowest average value found was 5.5mm on the right side and the highest average value found was 7.13mm on the left side. Considering the mean values obtained at the points of the retromolar triangle mucosa measured in this study, we conclude that the retromolar triangle shows thick mucosa, so the mini-implants indicated for this region should have a long transmucosal neck.

El trígono retromolar es un área triangular ubicado en la mandíbula, posterior al último molar. Esta región, debido al grosor y densidad ósea que presenta, es utilizada para la instalación de dispositivos que ofrezcan un sistema de anclaje para el movimiento de los molares inferiores. El objetivo de esta investigación es ofrecer datos morfométricos del grosor de la mucosa de región del trígono retromolar. Se utilizaron 25 pacientes de nacionalidad portuguesa, con indicación de exodoncia del tercer molar inferior retenido (derecho y/o izquierdo). En la región del trígono retromolar fueron demarcados 3 puntos correspondientes a los vértices de un triángulo cuya base se quedaba dirigida hacia la cara distal del tercer molar inferior y el largo de las vertientes correspondían a la dimensión vestíbulolingual del mismo diente; luego fue demarcado un cuarto punto correspondiente al centro geométrico del triángulo. Con un espaciador digital puntiagudo con tope de silicona incorporado se hizo la medición del grosor de la mucosa en cada punto. Los datos obtenidos fueron tabulados y analizados. El menor valor promedio encontrado fue 5,5mm en el lado derecho y el mayor fue 7,13mm en el lado izquierdo. Considerando los valores promedios obtenidos en los puntos de la mucosa, concluimos que la región del trígono retromolar presenta una mucosa gruesa, por lo tanto, los mini implantes indicados para esta región deben tener cuello transmucoso largo.
Study of the mucosa thickness of the retromolar triangle to facilitate the installation planning of mini-implants in the region
Keywords: Retromolar triangle; Mini-implants; Morphometry; Trígono retromolar; Mini implantes; Morfometría